Regulation of the Immune Balance During Allogeneic Hematopoietic Stem Cell Transplantation by Vitamin D - Flamann, Cindy; Peter, Katrin; Kreutz, Marina; Bruns, Heiko (Frontiers in Immunology, 2019)
One of the most promising therapeutic approaches for numerous hematological malignancies represents the allogeneic hematopoietic stem cell transplantation (allo-HSCT). One major complication is the development of the life-threatening graft-versus-host disease (GvHD) which limits beneficial effects of graft-versus-leukemia (GvL) responses during allo-HSCT. Strengthening GvL effects without induction of severe GvHD is essential to decrease the relapse rate after allo-HSCT. An interesting player in this context is vitamin D3 since it has modulatory capacity in both preventing GvHD and boosting GvL responses. Current studies claim that vitamin D3 induces an immunosuppressive environment by dendritic cell (DC)-dependent generation of regulatory T cells (Tregs). Since vitamin D3 is known to support the antimicrobial defense by re-establishing the physical barrier as well as releasing defensins and antimicrobial peptides, it might also improve graft-versus-infection (GvI) effects in patients. Beyond that, alloreactive T cells might be attenuated by vitamin D3-mediated inhibition of proliferation and activation. Despite the inhibitory effects of vitamin D3 on T cells, anti-tumor responses of GvL might be reinforced by vitamin D3-triggered phagocytic activity and antibody-based immunotherapy. Therefore, vitamin D3 treatment does not only lead to a shift from a pro-inflammatory towards a tolerogenic state but also promotes tumoricidal activity of immune cells. In this review we focus on vitamin D3 and its immunomodulatory effects by enhancing anti-tumor activity while alleviating harmful allogeneic responses in order to restore the immune balance.